Over easy - Pond, Mimi (Drawn and Quarterly, 2025)
"After being denied financial aid to cover her last year of art school, Margaret takes a waitressing job at local Oakland fixture: the Imperial Café. Here an impressionable young woman transforms into the worldly Madge as she is introduced to the wisecracking, fast-talking, drug-binging cooks, dishwashers, and waitstaff in her new life. At first she mimics these new and exotic grown-up friends, trying on the guise of adulthood with some awkward but funny stumbles. Gradually she realizes that these adults she idolizes are a mess of contradictions, misplaced artistic ambitions, sexual confusion, dependencies, and addictions."